Drifting in the Caribbean: Hints from the intertidal bivalve Isognomon alatus. (31st October 2019) - Leal, Inês; Flores, Augusto A.V.; Collin, Rachel; Tremblay, Réjean
Abstract: Settlement of most marine benthic invertebrates is intrinsically linked to the end of the pelagic life, but for a few, the transition to the benthos can be less well-defined. Early metamorphosed postlarvae of temperate and subtropical bivalves are known to delay final settlement, i.e., undergo secondary migrations, until detecting specific habitat cues. Here, we test the hypothesis that postlarval drifting occurs as well in tropical systems, being mediated by the nutritional quality of nearshore waters. We monitored early stages of the flat tree oyster Isognomon alatus on the Caribbean coast of Panama, and observed successive numerical dominance of late-stage larvae (pediveligers) and postlarvae (juvenile drifters) of this isognomonid in the water column. Of all the pelagic individuals collected, 19% corresponded to juvenile drifters, suggesting that conditions favoring juvenile drifting were present at the time of sampling and/or juvenile drifting may be commonplace for this species. During 23 consecutive sampling days, we detected a single settlement peak of long-term drifters that followed a decrease in sea-surface salinity. The shell morphology of juveniles revealed that first settlement for I. alatus takes place after theoretical competence, when prodissoconch II exceeds c. a. 300 μm. A shift in nearshore trophic conditions was detected after settlement, with particulate matter dominated by tracers of microalgae and vascular plant matter shifting to tracers for detritic matter and bacterial load. Essential fatty acids comprised 28% of the seston, yet, were minimally accumulated by I. alatus pediveligers (2% of energetic reserves). We highlight the importance of accounting for juvenile drifters of I. alatus on settlement estimates, as the spatial distribution of late larval stages and/or early settlers might not reflect their final distribution. This information is key to manage, exploit and/or conserve natural stocks. Graphical abstract: Image 1 Highlights: We report the prevalence of juvenile drifting in the Caribbean flat-tree oyster. First settlement takes place after theoretical competence (≈300 μm PII shell). Shifts in nutritional status of nearshore waters over a fine temporal scale (days). Essential fatty acids minimally accumulated by larvae (2% of lipid reserves). Initial settlement may be a poor indicator of I. alatus recruitment at small scales.